Democracy in Jeopardy: An Analysis of the Prospects of Opposition Political Parties in Nigeria’s Fourth Republic - Amos Olajubu (Goodwood Publishing, 2022)
Purpose: Opposition political parties are generally believed to be weak in Africa and particularly in Nigeria. Despite their centrality to the democratic consolidation, opposition parties are not performing the critical role as watchdogs to the ruling party partly because of their sizes or fragmentations. This study examined the role of the ruling political party in Nigeria and, by extension, the Nigerian government in making opposition parties be perpetually weak to ensure its hold on power. Research methodology: The study employed qualitative data in carrying out the research. Results: From the contextual analysis of the literature reviewed, the study discovered that weak political institutions and a lack of political will are largely at the heart of the problem in Nigeria. Recommendations: It posited that transparency and political will on the part of the ruling party and the government will create a level playing field for all political parties to thrive.